2014
DOI: 10.5617/osla.711
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation between translators in the use of clause building and clause reduction

Abstract: Recent years have seen an increasing interest in translators’ voices as manifested in their writing style. The present study is an investigation of differences in the use of clause building and clause reduction, which has not so far been investigated in any depth with regard to individual variation. The findings show that translators have distinct styles both with respect to how closely they follow the source text and in the structures they prefer when they introduce changes. The study also demonstrates the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In view of this, it is not surprising that English translators often build clauses (cf. Dirdal, 2014) from phrases in translations from German. The tendency for clause building is nevertheless strong enough for Swedish translators to also build clauses in translations from German, in spite of their generally more cautious approach to the introduction of changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In view of this, it is not surprising that English translators often build clauses (cf. Dirdal, 2014) from phrases in translations from German. The tendency for clause building is nevertheless strong enough for Swedish translators to also build clauses in translations from German, in spite of their generally more cautious approach to the introduction of changes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Dirdal, 2014;Ström Herold and Levin, 2018, forthcoming) have observed that translations tend to use more elaborate structures than originals, meaning that translators tend to go from phrasal to clausal constructions rather than the other way around. Dirdal (2014: 122) uses the term 'clause building' for those changes that move towards independent main clauses, such as phrases rendered as clauses or non-finite clauses rendered as finite clauses.…”
Section: Clause Building and Clause Reduction In Translationsmentioning
confidence: 96%
See 2 more Smart Citations